Antidiabetic drug utilization pattern, affordability and cost analysis in Iran from 2009 to 2021: A need to revise guideline - Saman Zartab; Hadi Abbasian (PLoS ONE, 2025)
Diabetes Mellitus is a chronic disease that has a notable prevalence and continues to rise. It has a significant economic burden and consumes lots of financial resources of the health sector, while about half of the diabetic patients have uncontrolled diabetes. Therefore, surveilling the utilization pattern and affordability of antidiabetic drugs is vital for appropriate policymaking. It was a retrospective descriptive study that evaluated the utilization of antidiabetic medications.. The Anatomical Therapeutic Classification (ATC) was applied to categorize medicine. The Anatomical Therapeutic Classification/Defined Daily Dose (ATC/DDD) methodology was used to calculate the number of consumed Defined Daily Doses (DDDs) and the number of DDDs per 1000 inhabitants per day (DID). The Drug Utilization 90% (DU-90) method was also used to determine the most used antidiabetic drugs and compare them with the WHO essential medicine list. The affordability of antidiabetic medicine was measured by comparing the one-month consumption price with the minimum daily wage. The utilization of antidiabetic drugs increased from 22.5 DID to 63.9 DID during the study period with a 9.05 Compound Annual Growth Rate (CAGR). The overall expenditure has increased by about 18 times. Expenditure analysis showed that the cost per DDD has increased significantly over the years. The DU-90 list completely matches the WHO essential medicine list. All human insulin products were affordable, while almost all insulin analogues were unaffordable until the last year of the study period. Most novel non-insulin antidiabetic products such as empagloflozin, sitagliptin and extended-release metformin were unaffordable during the study period. The utilization of antidiabetic drugs has increased substantially. The expenditure on antidiabetic drugs has grown more rapidly than the utilization of these drugs. The number of unaffordable medicines increased during the study due to the introduction of some novel antidiabetic drugs. Therefore, it is important to revise the diabetes guidelines to promote rational drug use.